APIs AND OPEN BANKING: DRIVING INTEROPERABILITY IN THE FINANCIAL SECTOR - Vijay Kumar Adari (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Open Banking projects and API interfaces are causing a paradigm change in the financial services sector that fundamentally changes the way banks, fintech companies, and outside vendors interact and exchange data. Examining the architectural foundations of Application Programming Interventions (APIs), which form the pillar of contemporary financial ecosystems and enable safe and consistent data interchange across many platforms, this thorough technical essay by means of a thorough analysis of legislative frameworks, implementation tactics, and actual applications, we investigate how Open Banking is transforming consumer financial management, improving security procedures, and so fostering financial inclusion. This article looks at the technological support for effective Open Banking implementations, including security systems, data standardizing techniques, and authentication methods. This article shows how API-driven interoperability is promoting innovation, increasing operational efficiency, and offering greater value to consumers while preserving strong security requirements by examining the change of banking architectures from closed systems to open platforms. This article emphasizes the important part of standardized APIs play in fostering financial sector innovation and proposes future paths for the development of interoperable banking services, especially with an eye toward the technical possibilities and challenges in establishing a more linked and inclusive financial ecosystem.